Plasma tumor necrosis factor alpha in obese and non-obese women with polycystic ovary syndrome - Mejía Montilla, Jorly (2016)
Objective: To determine plasma concentration of tumor necrosis factor alpha (TNF-alpha) in obese and non-obese women with polycystic ovary syndrome (PCOS). Design: Case control study. Participants: Women with diagnosis of PCOS and age-matched healthy controls, the latter with regular periods and normal ovaries according to ultrasound. Interventions: Participants were divided in four groups (group A: PCOS and obese; group B: PCOS and nonobese; group C: obese controls; and group D: non-obese controls) according to body mass index (obese > 30 kg/m2 y and non-obese < 25 kg/m2). Main outcome results: Concentrations of luteinizing hormone, follicle-stimulating hormone, androstenodione, testosterone, sex hormone-binding globulin, serum glucose, insulin and TNF-alpha. Results: Obese and non-obese women with PCOS had higher luteinizing hormone, follicle stimulating hormone, androstenodione. testosterone, and insulin levels compared to women in the obese and non-obese control group, respectively (p < 0.0001). Women with PCOS had a significantly higher TNF-alpha plasma concentration (group A 6.6 +/- 1.2 pg/mL and group B: 4.0 +/- 0.7 pg/mL) as compared with controls (group C: 4.4 +/- 1.3 pg/mL and group D 2.1 +/- 0.4 pg/dL; p < 0.0001). TNF-alpha concentrations presented a positive and significant correlation with fasting glycaemia and insulin in women with PCOS (p < 0.0001). Conclusion: There were significant differences in plasma TNF-alpha concentrations between obese and non-obese women as compared with polycystic ovary syndrome and normal controls.